2014
DOI: 10.1016/j.bpj.2014.09.023
|View full text |Cite|
|
Sign up to set email alerts
|

Penetration of Cell Membranes and Synthetic Lipid Bilayers by Nanoprobes

Abstract: Nanoscale devices have been proposed as tools for measuring and controlling intracellular activity by providing electrical and/or chemical access to the cytosol. Unfortunately, nanostructures with diameters of 50-500 nm do not readily penetrate the cell membrane, and rationally optimizing nanoprobes for cell penetration requires real-time characterization methods that are capable of following the process of membrane penetration with nanometer resolution. Although extensive work has examined the rupture of supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 58 publications
6
60
0
Order By: Relevance
“…Low penetration rate was obtained in experiment 1 by using the pyramidal nanotip, which was comparable to other reports . Most successful cases occur when the trigger force exceeds the insertion force.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Low penetration rate was obtained in experiment 1 by using the pyramidal nanotip, which was comparable to other reports . Most successful cases occur when the trigger force exceeds the insertion force.…”
Section: Resultssupporting
confidence: 88%
“…The molecules were coated on the surface of the nanoneedle, which could be transferred into the cell after the nanoneedle was successfully inserted into the cell membrane. However, the living cell is highly challenging to be inserted due to the complex internal structure and the interaction between the tip and the cell membrane, which is the main obstacle in the practice of cell transfection and intracellular studies by using the AFM‐nanotip technology . The insertion efficiency varies from 20 to 80% for different types of the cells, different nanofilms on the cell surface, and different environmental temperatures .…”
Section: Introductionmentioning
confidence: 99%
“…Kagiwada et al used single‐nanoneedle penetration experiments to argue that the actin meshwork reduces membrane fluidity, and is necessary to give the mechanical properties required for penetration . Although this finding was later disputed by Angle et al who found that they could rupture the cell membrane (of cells without an actin meshwork) by continuing to probe the cell well beyond just the initial indentation . Aalipour et al found that when cells are seeded onto nanostraws, this same meshwork can instead act as a barrier.…”
Section: Understanding the Cell–nanostructure Interfacementioning
confidence: 99%
“…Even without deliberate coating of these materials, proteins in cell culture medium can spontaneously undergo physisorption onto surfaces during cell culture, altering the perceived surface chemistry and binding sites seen by cells . Whether these materials actively or passively promote penetration is an open question; Angle et al found that coating a range of membrane‐related peptides onto single nanoneedle probes did not yield a corresponding change in the force required to manually penetrate the membrane in single‐cell experiments …”
Section: Fabrication Techniquesmentioning
confidence: 99%
“…These include MEA constructed by vertical micro12 or nano-electrodes (nanowires) that either penetrate the plasma membrane of excitable cells like sharp electrodes7131415161718, or nano-transistor based MEAs that are mechanically manipulated into the cells19202122. Iintracellular recordings from cultured cells by MEA technologies of vertical nanowires (nanopillars) and nanotransistors have been conducted on cultured primary cardiomyocytes1217202122 cultured LH-1 cell lines121718, the CHO cell line7 and HEK-293 cells1415. Nevertheless, the dimensions, adhesion and growth patterns of primary cultured mammalian neurons and the above-mentioned cell types differ substantially.…”
mentioning
confidence: 99%